A Beam of Light: Media, Tourism & Economic Development - Samuel Nocito; Marcello Sartarelli; Francesco Sobbrio (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Tourism accounts for around one tenth of global GDP. We analyze the impact of entertainment media in drawing tourists to filming locations (media multiplier ) and, in turn, the effect of tourism on local economic development (tourism multiplier ). To assess the media multiplier, we employ a triple-difference empirical strategy exploiting the staggered international release across the EU of Inspector Montalbano, a TV series set in four municipalities of Sicily, a region of Italy. We find that the series release led to a fourfold increase in the number of tourists and boosted tourist expenditure by a factor of 2.5. Furthermore, we provide evidence of positive spillovers in nearby municipalities. To estimate the tourism multiplier, we exploit the interaction between the filming locations and the time-varying share of countries in which the series was aired, to instrument total tourist expenditure at the municipality-time level. Our results show that a 10% increase in total tourist expenditure translates into an increase in municipal income of 4.7%. The paper suggests that both entertainment media and tourism can be powerful tools to boost economic development.
Keywords: L82; L83; O12; Z32; 330; media; tourism; economic development